ANALYSIS OF LABOR MARKET FORMATION IN UZBEKISTAN AND THEIR CURRENT STATUS (World Economics and Finance Bulletin, 2022)
In addition to highlighting the socio-economic nature of the labor market, the article discusses scientific methods in studying the formation of the labor market and the specifics of unemployment. The analysis of the state of the labor market in the Republic of Uzbekistan uses the method of correlationregression analysis and draws conclusions on the study of the formation and current state of the labor market of the Republic of Uzbekistan.